The Role of External Monitoring in Enhancing the Academic Quality in Secondary Schools - Lubna Huma Naz (Corresponding Author); Jam Muhammad Zafar; Naeemullah (Al-Qanṭara, 2024)
This research aims to investigate the impact of external evaluation and monitoring in enhancing the academic excellence of secondary schools in Punjab and to emphasize the value and advantages of these practices in enhancing academic quality. According to Lodhi, F. A., and Faizi, W. N. (2009:1–11), every member of a nation has the fundamental right to a high-quality education, hence it is regrettable that Pakistan's educational standards are deteriorating as each day of the academic year goes by. Goal 4 of Sustainable Development Agenda emphasizes providing everyone with access to high-quality, inclusive education for the formation of people and civilizations. It is a challenging task to guarantee that education fulfills the greatest criteria of quality, nevertheless. This is where assessment and monitoring come into play, offering crucial instruments to gauge and raise educational standards. In many nations around the world, Effective and successful system for monitoring and evaluation coupled with a robust accountability mechanism have demonstrated positive outcomes in recent years. Punjab province, established a special academic monitoring body in public schools to raise the standard of instruction by monitoring quality indicators. The study uses both qualitative and quantitative datasets, involving 429 participants from three Punjab regions: Faisalabad, Rahim Yar Khan, and Rawalpindi, to target principals, teachers, and MEAs in 20 public secondary schools. The researcher also discussed the instruments with the supervisor to ascertain their validity. The researcher utilized stratified sampling techniques, using two questionnaires for data collection from heads, teachers, and MEAs, and conducted interviews with CEOs, DEOs, and DMOs, after ensuring validity. Reliability was ensured by calculating the Cronbach coefficient. The study offers valuable insights into the impact of assessment and monitoring on improving academic excellence in secondary schools, aiding policymakers in formulating effective monitoring and evaluation processes. The data, analyzed using SPSS, found that staff inspections have reduced absenteeism among teaching and non-teaching workers, suggesting that school monitoring can enhance education standards. The study suggests reformation of Monitoring, focusing on standard assessments, and teachers' professional training identified by MEAs and MEAs professional training, as staff inspections resulted in reduced absenteeism rates. The absence of essential amenities at the school level was also noted by the researcher. This study's findings could inform the Ministry of Education and other stakeholders about the effectiveness of strategy implementation on academic performance in secondary schools. The study suggests that the government should invest in employee training on M&E tools, allocate adequate funds, and practice accountability. It also recommends stakeholder involvement in the M&E process, proactive design of M&E systems, and timely guidance. Further research is recommended to assess different thematic areas.